Contentious urban housing politics in European metropolises between financialisation, dispossession and re-possession. - Wehrhahn, Rainer (Springer VS, 2019)
The paper discusses pivotal questions of housing and housing policy after decades of liberalisation, deregulation and privatisation in urban (housing) politics. The focus is on European metropolises, where the impacts of these long-term processes together with the consequences of current financialisation processes have led to the dispossession of poorer urban social groups and to widespread discontentedness of both lower and middle-income groups. Protests and the rise of more or less powerful social movements, e.g. in Spanish and German big cities, criticising particularly urban housing politics, have resulted in a gradual rethinking of social responsibility and in the soft implementation of new (or recycled) instruments in favour of limiting capitalist interests. The discussion reviews the fundamental thoughts of housing-related urban development from a critical perspective, proposes conceptual frameworks for further studies that take structural as well as agency concepts into account, debates how to tackle contentious processes of eviction and dispossession, and presents initial approaches of re-possession in the light of new housing politics.
Keywords: Stadt; Großstadt; Wohnungsbedarf; Wohnungsversorgung; Wohnungsnot; Mietpreis; Segregation; Kommunale Wohnungspolitik; Stadtentwicklungspolitik